Advanced oxidation of real sulfamethoxazole + trimethoprim formulations using different anodes and electrolytes. (February 2018) - Murillo-Sierra, Juan C.; Sirés, Ignasi; Brillas, Enric; Ruiz-Ruiz, Edgar J.; Hernández-Ramírez, Aracely
Abstract: A commercial sulfamethoxazole + trimethoprim formulation has been degraded in 0.050 M Na2 SO4 at pH 3.0 by electrochemical oxidation with electrogenerated H2 O2 (EO-H2 O2 ), electro-Fenton (EF), photoelectro-Fenton with a 6-W UVA lamp (PEF) and solar photoelectro-Fenton (SPEF). The tests were performed in an undivided cell with an IrO2 -based, Pt or boron-doped diamond (BDD) anode and an air-diffusion cathode for H2 O2 electrogeneration. The anode material had little effect on the accumulated H2 O2 concentration. Both drugs always obeyed a pseudo-first-order decay with low apparent rate constant in EO-H2 O2 . Much higher values were found in EF, PEF and SPEF, showing no difference because the main oxidant was always OH formed from Fenton's reaction between H2 O2 and added Fe 2+ . The solution mineralization increased in the sequence EO-H2 O2  < EF < PEF < SPEF regardless of the anode. The IrO2 -based and Pt anodes behaved similarly but BDD was always more powerful. In SPEF, similar mineralization profiles were found for all anodes because of the rapid removal of photoactive intermediates by sunlight. About 87% mineralization was obtained as maximum for the powerful SPEF with BDD anode. Addition of Cl − enhanced the decay of both drugs due to their quicker reaction with generated active chlorine, but the formation of persistent chloroderivatives decelerated the mineralization process. Final carboxylic acids like oxalic and oxamic were detected, yielding Fe(III) complexes that remained stable in EF with BDD but were rapidly photolyzed in SPEF with BDD, explaining its superior mineralization ability. Highlights: Mixture of drugs treated with an IrO2 -based, Pt or BDD anode and an air-diffusion cathode. Larger degradation in sulfate medium: EO-H2 O2  < EF < PEF < SPEF, regardless of the anode. Quicker degradation using the BDD/air-diffusion cell in all methods. Similar apparent rate constants for EF, PEF and SPEF due to main attack of OH in the bulk. Presence of Cl − : enhanced drug decay due to active chlorine, but slower mineralization.